New bioeroding sponges from Mingulay coldwater reefs, north-west Scotland - Van Soest, R.W.M.; Beglinger, E.J. (Journal of the Marine Biological Association of the United Kingdom, 2009)
The relatively shallow coldwater coral reefs growing off the eastern coast of Mingulay, north-west Scotland, are excavated by five sponge species, three of which, Alectona millari, Pione vastifica and Cliona lobata, were known previously from Scottish waters. The other two species are new to Scotland and Great Britain. One species is here described as new to science: Cliona caledoniae sp. nov. The species shows a superficial resemblance in colour (orange) and spiculation (possession of tylostyles and knobby microscleres) to Cliothosa hancocki described disjunctly from the Pacific Ocean and the Mediterranean Sea, but it differs clearly in lacking the characteristic Cliothosa amphiasters with branching rays. The Scottish species only possesses peculiar thick-rayed streptasters, which at first glance appear rather similar to the second microsclere type reported for Cliothosa hancocki, knobby-rayed amphiasters. However, the majority of the microscleres in the Mingulay species appear to be genuine spirasters (not amphiasters), and exhaustive search for true amphiasters, branching or otherwise, was in vain. The new species is extensively illustrated. Furthermore, we also report the first occurrence in British waters of Spiroxya levispira, originally described from Azorean deep waters, and subsequently reported from Madeira and several Mediterranean localities. It was found to occur not uncommonly in the Mingulay reefs, and additionally also in reefs of the Rockall Bank, west of Ireland. The spicular characters generally match those of the southern locations. The newly recorded species is described and amply illustrated.